2020
DOI: 10.1177/1098612x20907171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a closed system and an open system for blood collection in feline donors

Abstract: Objectives This research aimed to evaluate the performance of a closed blood collection system and to compare it with an open system in terms of feasibility, tolerability by the donor, quality of blood collected and bacterial contamination. Methods Eight feline blood donors were prospectively and randomly subjected to both collection methods. Heart rate (HR), respiratory rate (RR) and blood pressure (BP) were evaluated before sedation, after sedation and after blood collection. The duration of the donation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Only one study (LOE 3, good) directly compared closed versus open systems in feline blood collection in terms of bacterial contamination in the blood units. 24 This study did not observe any difference in bacterial contamination between the two collection systems.…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 48%
See 2 more Smart Citations
“…Only one study (LOE 3, good) directly compared closed versus open systems in feline blood collection in terms of bacterial contamination in the blood units. 24 This study did not observe any difference in bacterial contamination between the two collection systems.…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 48%
“…Many papers (LOE 3, fair to good) reported bacterial contamination of feline blood units collected both with open, semi‐closed, and closed systems. Most studies were not able to demonstrate the source of bacterial contamination 22,24–26 . Only one study found the source of contamination of feline whole blood (WB) units with Serratia marcescens , which was alcohol‐soaked cotton balls used during skin preparation and a saline solution used during venipuncture of donor cats 27 .…”
Section: Domain 1: Prevention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, transfusion with a large load of endotoxin‐producing gram‐negative bacteria can cause rapid death in healthy individuals. In veterinary patients, the clinical outcome of transfusion of bacterial contaminated units has ranged from no reaction; 131,141,144 vomiting, collapse, diarrhea, icterus, panting, pyrexia/fever, abscess; 144 hypotensive shock syndrome; 149 and death. 144 In a case series of 15 Serratia marcescens contaminated units administered to 14 cats, 6 developed clinical signs of a transfusion reaction and 4 of these cats died.…”
Section: Transfusion‐transmitted Infection (Tti)mentioning
confidence: 99%
“…Another closed feline blood collection system was recently evaluated that permits blood collection by suction using a vacuum chamber; this accelerated the process without being detrimental to the blood donor or collected blood, therefore optimising collection. 89 In addition, the study directly compared this closed system with an open system for evidence of bacterial contamination of the units, and did not observe any difference between the two collection systems. 89 In a separate study, blood units and blood products collected using open systems were stored successfully for 35 days without microbial growth, although all blood banking was performed by experienced staff and blood was collected with appropriate aseptic collection methods, processing and careful storage to prevent contamination, 90 which may have contributed to this result.…”
Section: Continued On Page 424 T F E L I N E B L O O D C O L L E C T ...mentioning
confidence: 98%